Peningkatan Literasi Keuangan dalam Pemilihan Produk Perbankan melalui Strategi Promosi - Kinanti, Nadya Arum; Wikartika, Ira (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity aims to improve students' financial literacy in selecting banking products through digital-based education. The target audience is students who require a better understanding of banking products. The methods employed include the preparation of educational materials, promotion via social media, and evaluation using purposive sampling questionnaires. The results indicated an increased understanding of banking products among students, heightened interest in utilizing digital financial services, and greater awareness of the importance of financial literacy. This activity also strengthened the relationship between students and banking institutions by providing easily accessible relevant information. The findings demonstrate the effectiveness of an educational approach in enhancing financial literacy.